Health and Social Care Staff Awareness of Menopausal Symptoms in Adults With Intellectual Disability: Results From a Survey - Jack Wilson; Niall O'Kane; Bernice Knight; Angelica Lindsey-Clark; Jessdeep Rai (BJPsych Open, 2024)
Aims Menopausal symptoms often go unrecognised in individuals with intellectual disability (ID). There is growing societal awareness of the impact of menopause on mental health, yet this has not been replicated in the ID population. In light of this, we wanted to establish the current levels of knowledge, confidence and skills of staff working in a specialist community intellectual disability service (CIDS). The findings from the survey may help identify ways of improving awareness of menopausal symptoms with individuals with ID.